Rituximab for Children With Difficult-to-Treat Nephrotic Syndrome: Its Effects on Disease Progression and Growth - Rezan Topaloğlu; Bora Gülhan; Kübra Çelegen; Mihriban İnözü; Mutlu Hayran; Ali Düzova; Fatih Ozaltin; Fatih Ozaltin; Fatih Ozaltin (Frontiers Media S.A., 2019)
Background: Since the early 2000s rituximab (RTX) has been thought of as an alternative treatment for steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS).Objective: This study aimed to determine the effects of RTX treatment on disease outcome and growth in pediatric SSNS and SRNS patients.Materials and Methods: The medical records of pediatric SSNS and SRNS patients that began RTX treatment at the mean age of 10.8 ± 5.1 years between 2009 and 2017 were retrospectively reviewed. Additionally, the effect of RTX on growth was evaluated based on patient height, weight, and BMI z scores.Results: The study included 41 children, of which 21 had SSNS and 20 had SRNS. Mean age at diagnosis of NS was 5.8 ± 4.7 years. Mean duration of post-RTX treatment follow-up was 2.3 ± 1.6 years. Among the SSNS patients, 6 and 11 patients were steroid free and calcineurin inhibitor free at the last follow-up visit, respectively. The 1-year cumulative steroid and calcineurin inhibitor doses both decreased after RTX treatment, as compared to before RTX (P = 0.001 and P = 0.015, respectively). The median height z-score at the time of RTX initiation was −1.2 and the median height z-score at the last follow-up visit was −0.6 (P = 0.044). The median BMI z-score decreased from 1.6 (IQR; 0.9-3.0) at the time RTX was initiated to 1.1 IQR; [(−0.7)−2.5] at the last follow-up visit (P = 0.007). At the last follow-up visit 4 SRNS patients had complete remission and 4 had partial remission. The 1-year cumulative steroid dosage in the SRNS patients decreased significantly after RTX, as compared to before RTX (P = 0.001). The median height z-score at the time of RTX initiation was −0.8 and the median height z-score at the last follow-up visit was −0.7 (P = 0.81). The median BMI z-score decreased from 0.3 at the time RTX was initiated to −0.1 at the last follow-up visit (P = 0.11).Conclusion: RTX has a more positive effect on disease outcome and growth in SSNS patients than in those with SRNS.